Juvenile Myelomonocytic Leukemia: Molecular Pathogenesis Informs Current Approaches to Therapy and Hematopoietic Cell Transplantation - Loh, Mignon L.; Dvorak, Christopher C. (Frontiers in Pediatrics, 2014)
Juvenile myelomonocytic leukemia (JMML) is a rare childhood leukemia that has historically been very difficult to confidently diagnose and treat. The majority of patients ultimately require allogeneic hematopoietic cell transplantation (HCT) for cure. Recent advances in the understanding of the pathogenesis of the disease now permit over 90% of patients to be molecularly characterized. Pre-HCT management of patients with JMML is currently symptom-driven. However, evaluation of potential high-risk clinical and molecular features will determine which patients could benefit from pre-HCT chemotherapy and/or local control of splenic disease. Furthermore, new techniques to quantify minimal residual disease burden will determine whether pre-HCT response to chemotherapy is beneficial for long-term disease-free survival. The optimal approach to HCT for JMML is unclear, with high relapse rates regardless of conditioning intensity. An ongoing clinical trial in the Children’s Oncology Group will test if less toxic approaches can be equally effective, thereby shifting the focus to post-HCT immunomanipulation strategies to achieve long-term disease control. Finally, our unraveling of the molecular basis of JMML is beginning to identify possible targets for selective therapeutic interventions, either pre- or post-HCT, an approach which may ultimately provide the best opportunity to improve outcomes for this aggressive disease.